Targeting performance and poverty effects of proxy means-tested transfers: Trade-offs and challenges - Stephan Klasen; Simon Lange (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2015)
In the absence of reliable and exhaustive income data, Proxy Means Tests (PMTs) are frequently employed as a cost-effective way to identify income-poor beneficiaries of targeted anti-poverty programs. However, their usefulness depends on whether proxies accurately identify the income poor. Based on Receiver Operating Characteristics (ROC)-analysis, we find that PMTs perform poorly in terms of identifying poor households in Bolivian data when transfers are targeted narrowly to the poor but that the true positive rate is highly responsive to increases in the proportion of beneficiaries. Using non-parametric regression- techniques, we show that the resulting leakage can largely be confined to the non-poor close to the poverty line. However, simulating the effect on poverty measures of a uniform transfer to beneficiaries across inclusion rates suggests that the largest poverty effect is attained with very narrow targeting. Hence, we find a trade-off between targeting accuracy and poverty effect.
Keywords: C52; I38; O21; 330; targeting; transfers; social assistance; proxy means tests; poverty; ROC-analysis; Latin America; Bolivia